Репортаж про святкування 75-річчя заснування Національного ботанічного саду ім. М.М. Гришка НАН України (14–17, 21 вересня 2010 року) - Smilyanets, N.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
Reporting devoted to 75th anniversary of the M.M. Grysh ko National Botanical Garden of the National Academy of Sciences of Ukraine, including Solemn meeting, International scientific conference “Plants introduction, conservation and biodiversity enrichment in botanical gardens and arboreta”, opening of new areas, meet with the veterans of Gardens are presented.